Occurrence characteristics of shale oil in the second submember of Da'anzhai Member of Jurassic Ziliujing Formation, central Sichuan Basin - Chenyu ZHANG; Ziyi LIU; Bin WANG; Shuaiqiang SHAN; Jianlin LU; Baohua WANG; Zongxin ZUO (Shiyou shiyan dizhi)
Although China has abundant lacustrine shale oil resources, their exploitation is challenging. Investigating the various occurrence states of shale oil in shale reservoirs provides value for the exploration and development of shale oil resources. With the shale in the second submember of Da'anzhai Member of Jurassic Ziliujing Formation of the central Sichuan Basin (the Da2 submember) as the research object, the study reveals the occurrence modes of shale oil under different states in various medium pores, through the implementation of the multi-temperature pyrolysis experiment, the observation of pore development characteristics under the scanning electron microscope and the analysis of the pore size distribution before and after oil washing. In the Da2 submember, the shale oil is mainly in the free state (0.42 to 10.88 mg/g), followed by the adsorption state (0.30 to 1.95 mg/g), as revealed by thermal simulation recovery. The reservoir space of shale includes organic pores (pore size: 2 to 600 nm), pyrite intergranular pores (pore size: 10 to 700 nm), shell pores (pore size: 20 to 1 000 nm), quartz/feldspar intergranular pores (pore size: 4 to 500 nm) and clay mineral intergranular pores (pore size: 4 to 500 nm). After oil washing, the results of nitrogen adsorption and high pressure mercury injection demonstrated a significant increase in pores with sizes of 2 to 30 nm and 60 to 1 000 nm, where most of shale oil is stored. Meanwhile, it was demonstrated that the shale oil in the Da2 submember mainly occurs in organic matter and pyrite by establishing a heat map of the relationship between the occurrence state of shale oil and the medium in the rock. Lastly, by fitting the content of shale oil in different occurrence states with the oil volume obtained before and after oil washing, the pore size range for shale oil accumulation in the study area was determined. The free state of shale oil in the Da2 submember primarily accumulates in pores of organic matter and pyrite with pore size of 60 to 700 nm, and the adsorbed state of shale oil mainly accumulates in the organic matter pores with pore size of 2 to 6 nm. In conclusion, this study presents a thorough examination of the occurrence characteristics of shale oil in Da2 submember, and it will support shale oil exploitation efforts in the area.